History and ideology : the Khalsa over 300 years - Grewal, J. S.; Banga, Indu.; Indian History Congress (New Delhi : Tulika, 1999)
Contributed papers on Sikh history; previously presented at the various sessions of Indian History Congress.
Includes bibliographical references (p. 211-224).
Keywords: Sikhs -- India -- History